Foot and mouth disease outbreaks in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In late 2000, several African countries were startled by an outbreak of foot and mouth disease (FMD). Besides a probably modest outbreak in the south of Mauritania, eastern and southern Africa were particularly badly hit by the highly contagious...